Pengaruh Budaya Organisasi Dan Motivasi Terhadap Komitmen Organisasional Dengan Kepuasan Kerja Sebagai Variabel Intervening Pada PT. P&P Lembah Karet - Rio Andika Putra (Journal Of Science Education And Management Business, 2022)
This study aims to examine how much influence organizational culture and motivation have on organizational commitment and job satisfaction. The method of collecting data is through surveys and distributing questionnaires, with a sample of 77 respondents obtained by the slovin formula at PT. P&P Lembah Karet Jl. By Pass as many as 330. The sampling technique is using non-probability sampling with purposive sampling. The analytical method used is correlation analysis, multiple linear regression and path analysis (Path Analysis) SPSS 21. The results obtained based on the partial test (t test) obtained that organizational culture and motivation partially have a significant effect on job satisfaction at PT. P&P Lembah Karet with (Sig < 0.05). And also the results of understanding based on the Partial Test (t test) obtained that Organizational Culture, Motivation, and Job Satisfaction partially have a significant effect on Organizational Commitment at PT. P&P Lembah Karet with (Sig < 0.05). The contribution of Organizational Culture and Motivation to Job Satisfaction is 58.9%, the remaining 40.1% is influenced by other variables outside this study. Then the contribution of Organizational Culture, Motivation, and Job Satisfaction to the Organizational Commitment variable is 80.5%, the remaining 19.5% is influenced by other variables outside of this study.